Reward Deficiency Solution System (RDS): A Tale of Three Scientists - Kenneth Blum; Rajendra D Badgaiyan; Mark S Gold (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2015)
Prior to 1990 there was a paucity of studies directed at psychiatric genetics and in fact there was only one study by Egeland et al. [1]. whereby an analysis of the segregation of restriction fragment length polymorphisms (RFLP) in an Old Order Amish population (pedigree) localized a dominant gene linked to a strong predisposition to manic depressive disease to chromosome 11 possibly tyrosine hydroxylase. This finding was retracted in 1989 by Kelsoe et al. [2]. Following these very early studies Blum and Noble and their respective groups reported on the first ever confirmed association of the dopamine D2 receptor gene (DRD2) and severe alcoholism [3]. While this sparked some controversy [4] it was confirmed [5] and remains the most widely studied gene in psychiatric genetics and lead to the development of an entire field of medicine (PubMed 8/8/14- 14,661) -known as Psychiatric Genetics.